Have European 'smart cities' initiatives improved the quality of their citizens' lives?. Issue 3 (16th August 2022) - Paskaleva, Krassimira; Cooper, Ian
Abstract : Over the last decade, the EU has promoted the use of Smart City initiatives (SCIs) to – amongst other goals – improve citizens' quality of life (QoL). This paper examines whether literature in the public domain contains empirical evidence validating the causal relationship posited between SCIs and QoL, asking: Have European 'smart city' initiatives improved the quality of their citizens' lives? A broadly based literature review was undertaken to discover whether those chronicling such initiatives report success – in terms of achieving the objectives/benefits they set themselves. The findings show that published evidence dealing with this causal relationship is scant. Existing literature is strong on upfront promotion of the need for SCIs but weak on what they have delivered on the ground. Like the meaning of QoL itself in SC initiatives, the 'benefits' delivered on this front are not unpacked. So, despite their decade long history, the performance of, and outcomes from European SC initiatives remain poorly understood – partly owing to the dearth of published evidence about these issues, compounded by the inadequate research designs adopted for such initiatives, with insufficient attention given to reporting on their implementation or to evaluations of what they have achieved in practice.